ANALYSIS OF THE EFFECT OF LOCAL TAXES, LOCAL RETRIBUTIONS, AND PROCEEDS FROM THE MANAGEMENT OF SEPARATED REGIONAL ASSETS ON THE LOCAL OWN-SOURCE REVENUE OF JAMBI CITY - Ardina; Putra, Wirmie Eka; Parmadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The title of this thesis is “The Effect of Local Taxes, Local Retributions, and Proceeds from the Management of Separated Regional Assets on Local Own-Source Revenue in Jambi City”. This study aims to analyze the effect of Local Taxes, Local Retributions, and Proceeds from the Management of Separated Regional Assets on the Local Own-Source Revenue (PAD) of Jambi City during the period 2015–2024. The background of this study is based on the importance of optimizing sources of Local Own-Source Revenue in supporting the implementation of regional autonomy and increasing the fiscal independence of local governments. PAD is one of the main indicators in assessing the financial capacity of a region in financing development and public services. The theoretical foundation in this study describes the concept of Local Own-Source Revenue along with its components based on the applicable laws and regulations, as well as theories regarding regional financial management. This study uses a quantitative method with a multiple linear regression approach through the SPSS 26 program using time series data. The secondary data used are the Budget Realization Reports of the Jambi City Government for the years 2015–2024. The analysis techniques used include the classical assumption test, partial test (t-test), and simultaneous test (F-test). Based on the results of the study, simultaneously Local Taxes, Local Retributions, and Proceeds from the Management of Separated Regional Assets have a significant effect on Local Own-Source Revenue. Partially, Local Taxes have a positive and significant effect on PAD, while Local Retributions and Proceeds from the Management of Separated Regional Assets show a smaller effect on PAD. The coefficient of determination indicates that the independent variables are able to explain most of the variation in PAD.